KONSULTASI DAN PEMBINAAN AWIG-AWIG DI DESA PAKRAMAN JUNJUNGAN KECAMATAN UBUD-GIANYAR - Parwata, A.A. G. Oka; Griadhi, K. Wirta; Wita, I N.; Jayantiari, I.G.A. Mas Rwa (Buletin Udayana Mengabdi; Vol 12 No 1 (2013): Jurnal Udayana Mengabdi, 2013)
As it is widely recognized that community empowerment in tertiary education provides a wide chance to keep in touch with the community members. This is in order to get new experience and to dedicate the knowledge for others. This community empowerment activity aims at guiding community members of Junjungan village in Gianyar Regency, Bali to reformat and to revise the substance of their traditional law. Traditional law which is known as awig-awig in Junjungan customary village has been documented in written form. It also has been used as the code of conduct for the community members of Junjungan customary village for 10 years. However, the awig-awig has yet not considered representative that it has not been responsive to represent the people’s need and development in the community. Besides, this village is located in a strategic area of Ubud which is known as one of the tourist centers in Bali. As a result, the revision of awig-awig that makes it more responsive to community development is significantly needed. The method utilized in this event is discussion and consultation in which the community members are actively involved in redesigning their awig-awig. The techniques on how to write the articles in the traditional law are also the main focus in this event. All community leaders and community members involved in this event and gave their support so that a new guidance in the revision of the awig-awig of Junjungan village is successfully made and redesigned. In addition, the event can be carried out on time based on its plan and timeline.